2014
DOI: 10.1016/s1995-7645(14)60004-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro antioxidant and apoptotic activities of Cyperus rotundus

Abstract: It appears that C. rotundus extracts exhibit a potential use as a natural antioxidant and an apoptosis inducer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…[28,49] The protoscolicidal effect of C.rotundus rhizomes may be related to the alkaloids compound, others workers proved the action of alkaloids in Sophora mooreroffiana seeds which showed efficiency against E.granulosus protoscoleces. [50] Moreover Soumaya et al, [33] showed in phytochemical study of C.rotundus extracts the presence of total poly phenol, flavonoids compounds and tannins, also they identified orientin as one among other flavonoids and they considered it has potential role in biological activity of the extracts and it may be influence the antioxidant and apoptotic activity specifically in the alcoholic extract. [51] In the present study, as far as the extracts were as crude form and probably contain many compounds which may act synergistically, so it is difficult to decide which compound is responsible for the protoscolicidal effect.…”
Section: -Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28,49] The protoscolicidal effect of C.rotundus rhizomes may be related to the alkaloids compound, others workers proved the action of alkaloids in Sophora mooreroffiana seeds which showed efficiency against E.granulosus protoscoleces. [50] Moreover Soumaya et al, [33] showed in phytochemical study of C.rotundus extracts the presence of total poly phenol, flavonoids compounds and tannins, also they identified orientin as one among other flavonoids and they considered it has potential role in biological activity of the extracts and it may be influence the antioxidant and apoptotic activity specifically in the alcoholic extract. [51] In the present study, as far as the extracts were as crude form and probably contain many compounds which may act synergistically, so it is difficult to decide which compound is responsible for the protoscolicidal effect.…”
Section: -Discussionmentioning
confidence: 99%
“…[42,61,62] Regarding C. rotundus and within this hypothesis, recent studies concluded that the aerial parts extract of this plant exhibit a potential use as antioxidant and apoptosis inducer and explained that the anti-proliferative effect of these extracts is due to induction of apoptosis and suggested the regulation of apoptotic genes may be controlled by their phenolic content, orientin is one of the main flavonoids identified in alcoholic extract. [33] Moreover, the result of Hu et al, [63] confirmed the presence of apoptosis and the existence of CED-3 like apoptotic gene in protoscoleces of E. granulosus and proved that H2O2and hexamenthasone can induce cell apoptosis of protoscoleces in drug-induced apoptosis mechanisms.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 93%
See 1 more Smart Citation
“…Phenolic compounds are very important plant constituents because they exhibit an antioxidant activity by inactivating lipid free radicals or preventing decomposition of hydroperoxides into free radicals. 21 The antioxidant potential of the extracts were determined by five methods namely DPPH assay, super oxide radical scavenging assay, nitric oxide radical scavenging assay, hydroxyl radical scavenging assay and reductive assay; cytotoxic activity was studied by using trypan blue exclusion method.…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical constituents of C. rotundus and Z. officinale have been studied extensively. C. rotundus contains quercetin, kaempferol, alkaloids, flavonoids, tannins, starch, glycosides, chalcones, gallic acid and p-coumaric acid [9, 10]. Z. officinale includes gingerol, paradols, and shogaol [11, 12].…”
Section: Introductionmentioning
confidence: 99%